Pokrzywdzony, poszkodowany i ofiara przestępstwa w prawie polskim: The aggrieved party, the sutterer and the victim of an offence in the Polish law - Wojciechowski, Ryszard; Chamernik, Jarosław (Management and Administration Journal, 2021)
This publication is presenting legal interpretative problems to the institution of "the aggrieved party, the aggrieved party and the victim of an offence" in practice of applying the particular part of the penal code on the example of the crime of the nonmaintenance.